Innovative Pedagogical Mechanisms for Improving the Quality of Education in Higher Education Institutions in the Context of Digital Transformation (Journal of Pedagogical Inventions and Practices, 2026)
In the context of rapid digital transformation, higher education institutions are facing significant challenges and opportunities related to improving the quality of education. Digital technologies are reshaping teaching methodologies, learning environments, assessment systems, and institutional management. This article examines innovative pedagogical mechanisms that contribute to enhancing educational quality in higher education under digital transformation conditions. The study analyzes modern digital tools, learner-centered approaches, blended and online learning models, learning analytics, and the development of digital competencies among teachers and students. Special attention is given to institutional strategies, pedagogical innovation, and the integration of information and communication technologies (ICT) into the educational process. The article concludes that the systematic implementation of innovative pedagogical mechanisms, supported by digital infrastructure and continuous professional development, significantly improves learning outcomes and educational quality in higher education institutions.